Attention biases in perfectionism: Biased disengagement of attention from emotionally negative stimuli - Tonta, Kate; Howell, Joel; Hasking, Penelope; Boyes, Mark; Clarke, Patrick (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
© 2019 Elsevier Ltd